THE IMPORTANCE OF A PSYCHOLOGICAL APPROACH IN TEACHING ENGLISH LANGUAGE TO YOUNG CHILDREN - Ismoilova Gulyora Murodjon qizi; Aminova Sohila Abduhalimovna (TADQIQOTLAR, 2025)
ABSTRACT:  Teaching English to young children requires more than linguistic methods;  it  necessitates  a  psychological  approach  that  considers  cognitive development,  emotional  engagement,  and  motivation.  This  article  explores  how psychological theories, such as Piaget’s cognitive development stages and Vygotsky’s socio-cultural theory, influence language learning. It also highlights the importance of creating  a  supportive,  engaging,  and  child-centered  learning  environment.  By integrating  psychological  principles,  educators  can  enhance  children’s  language acquisition,  boost  confidence,  and  foster  long-term  interest  in  learning  English. Practical  applications,  such  as  play-based  learning,  scaffolding,  and  multisensory teaching methods, are also discussed.